MANFAAT PSIKOLOGI PENDIDIKAN BAGI PENDIDIK - Loeziana Uce; Sri Wahyuni (ADIBA : JOURNAL OF EDUCATION, 2025)
This research aims to determine the benefits of educational psychology for educators in improving the quality of learning. The problem faced by educators today is a lack of understanding of educational psychology which can affect the quality of learning. The aim of this research is to determine the benefits of educational psychology for educators in improving the quality of learning. The research method used is literature study by analyzing various relevant literature sources. The research results show that educational psychology has significant benefits for educators in improving the quality of learning, namely increasing educators' ability to understand student behavior and needs, increasing learning effectiveness, and improving the quality of relationships between educators and students.